Aggressive behaviors between residents with dementia in an assisted living residence. (July 2015) - Caspi, Eilon
Aggressive behavior between residents with dementia in long-term care residences is a concerning but understudied phenomenon. The goal of the study was to identify the circumstances, sequence of events, and triggers that lead to these behaviors. I collected the data during 10 months in two special care units of an assisted living residence. I used participant observation as the primary data collection strategy, complemented by review of clinical records and semi-structured interviews with care staff and managers. As the analytic framework, I used Grounded Theory informed by Miles and Huberman's approach. In a substantial number of the reported 85 incidents, I identified observable early warning signs; in the majority, I identified observable causes or triggers prior to the aggressive acts. The majority of incidents were situational-reactive (circumstance-driven) and therefore potentially modifiable. Twelve effective staff prevention strategies were identified. I suggest incorporating the study findings into care staff training programs.